Pro-inflammatory Cytokine TNF-α Reduces Matrix Calcification in Papillary Thyroid Carcinoma - Fu, Junyi; Fu, Junyi; Niu, Jianhua (Indian Journal of Pharmaceutical Education and Research, 2026)
Aim/Background: Tumor Necrosis Factor-α (TNF-α) is a key pro-inflammatory cytokine involved in immune regulation, chronic inflammation, and tumor progression. However, its role in the calcification process of thyroid malignancies, particularly Papillary Thyroid Carcinoma (PTC), remains unclear. To investigate the effect of TNF-α on matrix calcification and the invasive behavior of papillary thyroid carcinoma cell lines. Materials and Methods: Two PTC cell lines, TPC-1 and BCPAP, were treated with varying concentrations of TNF-α. The expression of the calcification marker Osteopontin (OPN) was measured. Alizarin Red and Alkaline Phosphatase staining were used to assess matrix calcification, while cell migration and invasion assays evaluated the malignant potential of the cells. Results: TNF-α treatment significantly reduced OPN expression in both TPC-1 and BCPAP cells (p < 0.05). Cells treated with 100 ng/mL TNF-α showed decreased calcification and increased invasive and migratory abilities compared to controls and the 1 ng/ mL TNF-α group (p < 0.05). Conclusion: TNF-α suppresses matrix calcification and enhances the invasive potential of PTC cells, suggesting a potential role in the progression and pathogenesis of calcification in thyroid cancer.
Keywords: Thyroid papillary carcinoma; Calcification; Inflammatory cytokines